2018
DOI: 10.1111/petr.13150
|View full text |Cite
|
Sign up to set email alerts
|

Significant correlation between peripheral blood CD34+ cell count in children prior to aphaeresis and CD34+ cell yield following aphaeresis: A single‐center experience

Abstract: Numerous adults' studies demonstrated that preaphaeresis CD34+ cells significantly correlate with the number of CD34+ cells collected by the aphaeresis procedure. Equivalent studies in children are scarce. We studied retrospectively 92 aphaeresis procedures performed following chemotherapy (44) or in steady state (48) in 60 pediatric patients (40 males, 20 females), median age of 7.5 years. Aphaeresis procedures were performed using a SPECTRA Optica (TERUMOBCT) continuous flow cell separator. CD34+ cell concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…In our study, we confirmed well‐known positive correlation between mobilized peripheral CD34+ cell count with CD34+ yield 17–19 . We have collected targeted 5 × 10 6 cells/kg by first‐day apheresis in more than 60% of patients with peripheral CD34+ cell count >10/μL.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In our study, we confirmed well‐known positive correlation between mobilized peripheral CD34+ cell count with CD34+ yield 17–19 . We have collected targeted 5 × 10 6 cells/kg by first‐day apheresis in more than 60% of patients with peripheral CD34+ cell count >10/μL.…”
Section: Discussionsupporting
confidence: 86%
“…In our study, we confirmed well-known positive correlation between mobilized peripheral CD34+ cell count with CD34+ yield. [17][18][19] We have collected targeted 5 × 10 6 cells/kg by first-day apheresis in more than 60% of patients with peripheral CD34+ cell count >10/ μL. Rujkijyanont et al 18 retrospectively studied the largest pediatric series with 396 apheresis procedures in 301 pediatric cancer patients and reported higher pre-apheresis peripheral CD34+ levels of >35 × 10 6 CD34+ cells/μL were strong predictor value for stem cell collection.…”
Section: Discussionmentioning
confidence: 99%